The Legal and Political Concept of Federalism and the Fair Distribution of Competincies - الاستاذ الدكتور عبدالغفور علي غفور; المدرس الدكتور شفان احمد عبدالقادر (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
As it is known, the federal state arise from accession of several countries, some of them to each other does nor think of a new state and one union state and have a constitution that distributes powers, wealth and responsibility legally and fairly between the states of the regions and states either lose these regions or states some of their sovereignty. The federal constitution distinguishes the powers between the regions and the center and in respect of wealth, responsibilities water, etc. in affair and legal manner and in accordance with the provisions of the constitution that retains some exclusive power and authority of federal states.